Virtual Assistance in The Pandemic Era for Residents of Gebang Putih to Process Household Organic Waste into Compost (Future Science, 2021)
The COVID-19 pandemic had become a situation that was enough to limit people's activities directly and avoid crowds as much as possible. Meanwhile, the need to continuously improve competence in managing waste was crucial to solving environmental problems. This paper aimed to describe the activities of assisting the making of compost for RW. 03 residents, Gebang Putih, Surabaya which was carried out virtually by using the WhatsApp group. This assisting activity was a follow-up activity from the previous offline training (Perwitasari, Fauziyah, & Mas’udah, 2021). To oversee the success of the Gebang Putih community's composting activities, the assistance was also carried out virtually. This WhatsApp group was a method that is quite effective in accommodating citizen questions and solutions provided based on discussions between group members. The satisfaction of using WhatsApp group as a means of assisting in composting was quite high, i.e., 81%. However, it was undeniable that several obstacles cannot be overcome through virtual assistance, including checking the ripe compost directly, not all training participants were willing to make compost independently at home. It was hoped that this mentoring activity will be one of the solutions for empowering residents in managing waste during the pandemic era.